Answer:
See below
Step-by-step explanation:
a. here you are to multiply the two functions together:
![(3x-1)(2x^{2} )=6x^{3}-2x^{2}](https://tex.z-dn.net/?f=%283x-1%29%282x%5E%7B2%7D%20%29%3D6x%5E%7B3%7D-2x%5E%7B2%7D)
b. here you are to subtract g from f:
![(3x-1)-(2x^{2})=-2x^{2}+3x-1](https://tex.z-dn.net/?f=%283x-1%29-%282x%5E%7B2%7D%29%3D-2x%5E%7B2%7D%2B3x-1)
c. here you are to compose g into f. In other words, pick up the whole g function and plug it into f wherever you see an x:
![3(2x^{2} )-1=6x^{2} -1](https://tex.z-dn.net/?f=3%282x%5E%7B2%7D%20%29-1%3D6x%5E%7B2%7D%20-1)
d. here you are compose f into g. In other words, pick up the whole f function and plug it into g wherever you see an x:
![2(3x-1)^2](https://tex.z-dn.net/?f=2%283x-1%29%5E2)
You now have to FOIL out the (3x-1) like so:
![2[(3x-1)(3x-1)]](https://tex.z-dn.net/?f=2%5B%283x-1%29%283x-1%29%5D)
which gives you
![2(9x^{2} -6x+1)](https://tex.z-dn.net/?f=2%289x%5E%7B2%7D%20-6x%2B1%29)
Distribute in the 2 and you'll end up with the answer:
![18x^{2} -12x+2](https://tex.z-dn.net/?f=18x%5E%7B2%7D%20-12x%2B2)
Answer:
18a(2bc + 3d)
Step-by-step explanation:
36abc + 54ad
Step 1: Find the Highest Common Factor of each
36abc = 2×2×3×3×a×b×c = 18a × 2bc
54ad = 2×3×3×3×a×d = 18a × 3d
HCF = 2×3×3×a = 18a
Step 2: Factor out with HCF
18a(2bc + 3d)
Answer:
4 14/15
Step-by-step explanation:
8 3/5 - 11/3
8 9/15 - 55/15
8 9/15 - 3 10/15
7 24/15 - 3 10/15
4 14/15
Answer:
1.) 5/4
2.) -4/5
3.) 1/4
4.) -1
5.) 1
Step-by-step explanation:
<u>Brainliest Please</u>
ANSWER:
128.79 x .30 = $38.64